A new species of ?Diploctenium (Anthozoa: Meandrinidae) from the Trihueco Formation (Lower Paleocene), south-central Chile - Collado, Gonzalo A.; Galleguillos, Fernando F. (Zootaxa, 2025)
The genus Diploctenium comprises extinct corals that inhabited Europe, Africa, and West Asia from the Upper Cretaceous to the Lower Paleocene. This paper presents the first formal description of a species of this genus in Chile. Named ?Diploctenium chilensis sp. nov., this fossil was discovered in the Trihueco Formation within the Arauco Basin in the south-central region of the country, dating back to the Paleocene. The new species bears resemblance to Diploctenium zuffardii, one of the youngest fossils of the genus found in the Maastrichtian Age near the end of the Late Cretaceous in Libya. ?Diploctenium chilensis sp. nov. is also the first species of the genus to be described from the Americas.